Assessment of hand hygiene practices among nurses at a regional hospital in Kandahar, Afghanistan: A cross-sectional study based on the World Health Organization (WHO) ‘Your 5 Moments for Hand Hygiene’ guidelines - Baseer, Abdul Qadeer; Usmani, Asmatullah; Mushfiq, Shafiqullah; Hassand, Mohammad Hassan; Rahimi, Bilal Ahmad; Monib, Abdul Wahid; Daqiq, Mohammad Salim; Niazi, Parwiz (Belitung Raya Publisher - Belitung Raya Foundation, 2025)
Background: Hand hygiene is a critical component of infection prevention and control (IPC) in healthcare settings, as emphasized by the World Health Organization (WHO). However, compliance with recommended hand hygiene practices remains suboptimal in many resource-limited settings, including Afghanistan. Despite its importance, limited research has been conducted on hand hygiene practices in Afghan healthcare facilities, highlighting the need for further investigation. Objective: This study aimed to evaluate the self-reported hand hygiene practices of nurses at Mirwais Regional Hospital in Kandahar, Afghanistan. Methods: A cross-sectional study was conducted among 141 nurses between August and October 2023. Self-reported hand hygiene compliance was assessed using WHO’s “Your 5 Moments for Hand Hygiene” framework. Data on demographic characteristics, training, and compliance rates were collected. Descriptive statistics and logistic regressions were applied to analyze the data using SPSS version 26.0. Results: The study found that 73.1% of nurses demonstrated good hand hygiene practices, while 26.9% had non-good compliance. Female nurses showed significantly higher compliance (87.5%) than their male counterparts (68.8%) with a p-value of 0.044, AOR = 1.15 (95% CI: 1.03–9.75). Nurses with a bachelor’s degree had higher compliance (92.3%) compared to those with a diploma (59.4%) (p = 0.046, AOR = 2.1, 95% CI: 0.15–0.96). Nurses aged ≥30 years showed better compliance (96%) than those aged 20–29 years (75.3%) (p = 0.006, AOR = 2.1, 95% CI: 1.84–36.53). Hand hygiene training was positively associated with better compliance (88.3% vs. 61.9%, p = 0.004, AOR = 1.5, 95% CI: 0.07–0.6). Conclusion: While overall compliance was relatively high, significant gaps persist, particularly among younger, less educated, and male nurses, as well as those in high-burden wards. Enhanced training programs, tailored strategies, and regular audits are essential for improving hand hygiene practices and strengthening infection prevention and control efforts, ultimately enhancing patient safety in resource-limited settings.